2021
DOI: 10.1161/strokeaha.119.027900
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Outcome After Ischemic Stroke

Abstract: Background and Purpose: A survival advantage among individuals with higher body mass index (BMI) has been observed for diverse acute illnesses, including stroke, and termed the obesity paradox. However, prior ischemic stroke studies have generally tested only for linear rather than nonlinear relations between body mass and outcome, and few studies have investigated poststroke functional outcomes in addition to mortality. Methods: We analyzed consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 40 publications
4
24
0
5
Order By: Relevance
“…In the subgroup analysis, we found that there was a significant sex difference in the inverse association between BMI and intracranial aneurysm rupture. Our sex-strata result is similar to several previous cardiovascular and cerebrovascular studies where they also observed that the inverse association between BMI and adverse events is more prominent in males than in females (Hong et al, 2018;Liu et al, 2021). This result may be partly explained by the fact that there is a sex difference in the prevalence of obesity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the subgroup analysis, we found that there was a significant sex difference in the inverse association between BMI and intracranial aneurysm rupture. Our sex-strata result is similar to several previous cardiovascular and cerebrovascular studies where they also observed that the inverse association between BMI and adverse events is more prominent in males than in females (Hong et al, 2018;Liu et al, 2021). This result may be partly explained by the fact that there is a sex difference in the prevalence of obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Traditionally, obesity has been regarded as a well-established risk factor for cardiovascular diseases and stroke. Nevertheless, a growing body of evidence has suggested that an "obesity paradox"-namely that there is an inverse association between obesity and clinical outcomes-exists for patients with hypertension (Kleinloog et al, 2018) coronary artery diseases (Uretsky et al, 2007;Wang et al, 2015), atrial fibrillation (Sandhu et al, 2016), intracerebral hemorrhage (Persaud et al, 2019), and ischemic stroke (Rodríguez-Castro et al, 2019;Liu et al, 2021). Likewise, this paradoxical phenomenon was also observed in patients with SAH (Rinaldo et al, 2019;Rautalin et al, 2020), suggesting a potential protective effect of increased BMI on the risk of adverse events after presenting intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…However, consistent with our results, Mutai et al also reported that in patients with acute stroke, BMI is negatively associated with reduced motivation immediately after acute stroke, which was one of the five dimensions of the multidimensional fatigue inventory (MFI) [19]. A possible explanation is that acute stroke produces nutritional challenge, with increased metabolic catabolism due to physiological stress, and reduced caloric intake associated with dysphagia and disability [11]. Stroke patients with high BMI have greater metabolic reserve, which may be better able to withstand the nutritional damage [45,46] to maintain the stability of physiological and psychological state.…”
Section: Longitudinal Analysessupporting
confidence: 90%
“…Obesity has become a global public health concern, and it directly or indirectly accounts for a large portion of health-related costs [10]. Overweight and obesity were not only important risk factors for stroke, but also related to disability and stroke-related quality of life [11]. In several studies, obesity has been associated with motor fatigue [12], cancer-related fatigue [13][14][15], chronic fatigue syndrome [16], and fatigue in patients with systemic lupus erythematosus (SLE) [17] and inflammatory bowel diseases [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that Caucasians and direct admission for treatment were associated with improving neurologic functions is consistent with other studies that show that Caucasian stroke patients [ 10 ] and direct admission [ 38 ] were associated with improved functional outcomes. In addition, our finding of an association between obesity and improving neurologic functions is similar to other studies on ischemic stroke [ 39 , 40 ], coronary artery disease, and congestive heart failure [ 41 , 42 ]. However, this finding needs to be cautiously interpreted, as we used a data analytical approach that does not allow the randomization of our data collection.…”
Section: Discussionsupporting
confidence: 91%